Plan de negocios para la creación de una empresa productora y comercializadora de conejos en la ciudad de Latacunga, periodo 2012 - Riera Osorio, Doris Elizabeth (2014)
The research objective of seeking to create a producer and marketer of rabbits company, taking into account that in the city of Latacunga there is an organization that is dedicated to this activity covers more than backyard flocks. Lack of knowledge to venture into opening a small business could be one of the causes which hinder entrepreneurship, also in the absence of a place where rabbits are raised in the city, drive the residents to travel to other destinations in search for products that meet their requirements. The methodology used for the development of the research will be both quantitatively and qualitatively to help me determine the demand, supply and unsatisfied demand for the product and this type of research helps me to establish the characteristics of the market that will be covered in the Latacunga….